2010
DOI: 10.4997/jrcpe.2010.108
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis following co-prescription of fusidic acid and atorvastatin

Abstract: Campbell for her help with this manuscript. 2010; 40:33-6 Rhabdomyolysis following co-prescription of fusidic acid and atorvastatin J R Coll Physicians Edinb

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The FA package insert and the medical literature suggests inhibition of CYP3A4 by FA as a likely mechanism of muscular side effects (Burtenshaw et al, 2008;Collidge et al, 2010;Teckchandani et al, 2010;Kearney et al, 2012), since CYP3A4 is principally responsible for the metabolic clearance of atorvastatin and simvastatin in humans (Lennernäs, 2003;Elsby et al, 2012). However, it is now widely recognized that the systemic clearance of statins such as atorvastatin, simvastatin, and rosuvastatin is predominantly determined by the hepatic uptake mediated by organic anion transporting polypeptides (OATPs; OATP1B1, OATP1B3, and OATP2B1) (Neuvonen et al, 2006;Kitamura et al, 2008;Zamek-Gliszczynski et al, 2009;König et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FA package insert and the medical literature suggests inhibition of CYP3A4 by FA as a likely mechanism of muscular side effects (Burtenshaw et al, 2008;Collidge et al, 2010;Teckchandani et al, 2010;Kearney et al, 2012), since CYP3A4 is principally responsible for the metabolic clearance of atorvastatin and simvastatin in humans (Lennernäs, 2003;Elsby et al, 2012). However, it is now widely recognized that the systemic clearance of statins such as atorvastatin, simvastatin, and rosuvastatin is predominantly determined by the hepatic uptake mediated by organic anion transporting polypeptides (OATPs; OATP1B1, OATP1B3, and OATP2B1) (Neuvonen et al, 2006;Kitamura et al, 2008;Zamek-Gliszczynski et al, 2009;König et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in countries where FA is available, chronic oral therapy with FA is routinely used in the treatment of Staphylococcus-mediated prosthetic joint infections among the elderly population (Aboltins et al, 2007;Wang et al, 2012). The widespread clinical use of FA in suppressive antibiotic therapy is also associated with several cases of life-threatening rhabdomyolysis (with fatalities) upon coadministration with the 3-hydroxy-3-methylglutaryl CoA reductase inhibitors, atorvastatin and simvastatin (Wenisch et al, 2000;Yuen and McGarity, 2003;Burtenshaw et al, 2008;O'Mahony et al, 2008;Herring et al, 2009;Saeed and Azam, 2009;Collidge et al, 2010;Magee et al, 2010;Teckchandani et al, 2010;Kearney et al, 2012;Gabignon et al, 2013), and more recently, rosuvastatin (Cowan et al, 2013). The package insert for sodium fusidate (Fusidin tablets) was also recently amended with additional warnings to reflect the adverse musculoskeletal findings (https://www.medicines.org.uk/emc/medicine/2448).…”
Section: Introductionmentioning
confidence: 99%
“…The patients' characteristics are similar to those of 18 previously reported cases (table 2⇓). [6][7][8][9][10][11][12][13][14][15][16][17] .…”
Section: Cohortmentioning
confidence: 99%
“…Approximately 30 cases of DDIs between FA and statins have been reported in the literature (3,(6)(7)(8)(9)(10)(11). Because the majority of the reports involved atorvastatin and simvastatin, which are known to be cleared primarily by cytochrome P450 3A4 (CYP3A4), and since there is some evidence of involvement of CYP3A4 in FA disposition, it was assumed that FA reduces the clearance of statins via inhibition of CYP3A4 (9-11).…”
mentioning
confidence: 99%
“…Because the majority of the reports involved atorvastatin and simvastatin, which are known to be cleared primarily by cytochrome P450 3A4 (CYP3A4), and since there is some evidence of involvement of CYP3A4 in FA disposition, it was assumed that FA reduces the clearance of statins via inhibition of CYP3A4 (9)(10)(11). Accordingly, it was suggested that statins which are primarily eliminated by CYP3A4 (atorvastatin and simvastatin) are more likely to result in DDIs when coadministered with FA than statins with minimal elimination by CYP3A4 (rosuvastatin, pravastatin, and fluvastatin) (10). However, there have been two reports with rosuvastatin (3,7), and alternative mechanisms for the DDIs have been proposed (12)(13)(14).…”
mentioning
confidence: 99%